The Transformation of Rumoh Aceh Philosophy in Educational Facilities of Balai Pengajian Quran in Aceh Besar - Zulhadi - Sahputra; Era Nopera Rauzi; Muhammad Heru Arie Edytia (Journal of Islamic Architecture, 2022)
The phenomena of the Acehnese traditional houses philosophy functioned as dwelling houses have shifted into simple educational building design concepts, particularly for the people who live in suburban. The concept is able to be implemented by modern society in Aceh in order to design government buildings, banking offices, and other public buildings. This study aims to identify and analyze how the philosophies of the Acehnese traditional dwelling are transformed into a modest educational facility. The focus area of study is educational facilities owned by the local community located in the suburbs. Is the level of comfort suitable for its function? The study used three stages of research methodology: (1) observation which was carried out by using a typomorphological approach; (2) analysis of elements of Acehnese traditional house construction; and (3) simulation of the factors that determine the comfort of the building. The results of this study indicate the possibility of adapting the traditional Acehnese house design concept into an educational facility. The front porch (Seuramoe Keue) of the space division in Rumoh Aceh can be transformed as Balai Pengajian Quran using wood as primary materials for construction and building.